Significado y comprensión en la historia de las ideas - Quentin Skinner (Prismas, 2000)
Título original: “Meaning and understanding in the history of ideas”, en James Tully (comp.), Meaning & Context. Quentin Skinner and his Critics, Princeton, Nueva Jersey, Princeton University Press, 1988, pp. 29-67. (Aparecido originariamente en History and Theory, Nº 8, 1969, pp. 35-53.) Traducción: Horacio Pons.